2022
DOI: 10.2337/dc22-1055
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Access and Use of Diabetes Technology Among Adult Patients With Type 1 Diabetes in a U.S. Academic Medical Center

Abstract: OBJECTIVE Recent studies highlight racial disparities in insulin pump (PUMP) and continuous glucose monitor (CGM) use in children and adolescents with type 1 diabetes (T1D). This study explored racial disparities in diabetes technology among adult patients with T1D. RESEARCH DESIGN AND METHODS This was a retrospective clinic-based cohort study of adult patients with T1D seen consecutively from April 2013 to January 2020. Race… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Despite the implementation of nationally and internationally agreed recommendations, it has been recognized that there are health care inequalities with regards to access and this includes access to all diabetes technologies. People with T1D from lower socio‐economic demographic and ethnic minority groups are less likely to access rtCGM and insulin pump systems 38,39 . Ongoing efforts to bridge these inequalities are being prioritized 40 …”
Section: Real‐time Continuous Glucose Monitoring Technologymentioning
confidence: 99%
“…Despite the implementation of nationally and internationally agreed recommendations, it has been recognized that there are health care inequalities with regards to access and this includes access to all diabetes technologies. People with T1D from lower socio‐economic demographic and ethnic minority groups are less likely to access rtCGM and insulin pump systems 38,39 . Ongoing efforts to bridge these inequalities are being prioritized 40 …”
Section: Real‐time Continuous Glucose Monitoring Technologymentioning
confidence: 99%
“…Only one new study has been published since the most recent review in this area (2022) ( 17 ). Kanbaour et al., 2023 conducted a retrospective clinic-based cohort study of 1,258 adults with T1D who received care between 2013-2020 ( 28 ). The authors report that, relative to non-Black adults, Black adults were less likely to use CGM at baseline and were less likely to initiate CGM over the study period.…”
Section: Disparities In Cgm Usementioning
confidence: 99%
“…Of relevance to CGM use, a few studies document provider implicit bias to recommend diabetes technology based on insurance ( 32 , 33 ) and race or ethnicity ( 33 ). Relatedly, a recent clinic-based retrospective study demonstrated that, relative to non-Black adults, Black adults with T1D were less likely to discuss CGMs with their providers and be prescribed a CGM than non-Black adults (see Table 1 ) ( 28 ). It is plausible that providers may eliminate CGM as an option for members of marginalized groups based on biases, stereotypes, and generalizations regarding factors such as health literacy, socioeconomic status, and social contexts affecting their ability to take on new treatment regimens; however, this is an area requiring further study.…”
Section: Disparities In Cgm Usementioning
confidence: 99%
“…Patients have reported that providers have ‘discouraged and blocked’ the use of technology due to ‘glycemic control’ concerns or perceptions of a ‘device being too complex for the patient’, even against their wishes [27 ▪▪ ]. There have also been reports of receiving infrequent discussions and incomplete information about the benefits of technologies [25,28 ▪ ]. Given that patients heavily rely on providers for knowledge and these recommendations regarding technology use [19 ▪▪ ], any limitations in these discussions could exacerbate disparities among these groups.…”
Section: Drivers Of Disparities In Diabetes Technology Usementioning
confidence: 99%